Social Capital of the Fragrant Root Oil Workers Community in Indonesia - Chotim, Endah Ratnawaty (International Journal of Psychosocial Rehabilitation, 2020)
Social capital is something very important in the survival of a group or individual. The strength of social capital can be known through elements that are embedded in the social structure of the community which includes trust, norms, and networks. This article discusses the social capital of fragrant root oil workers in Garut Regency, Indonesia. This study uses qualitative methods with data collection techniques such as in-depth interviews and documentation studies. Data analysis was performed using the Miles & Huberman model. This study found that social capital formed in the fragrant oil worker environment is social capital that grows from active participation, trust, cooperation, and reciprocity.